1、
sina+(sina)^2=1
=>
sina=(cosa)^2
=>
(cosa)^2+(cosa)^4
=sina+(sina)^2
=1
2、
(sina+cosa)^2
=1+2sinacosa
=1+(sin2a)
=1+1/2=3/2
=>
sina+cosa=正负√(3/2)
3、
tana+cota=3
=>
sina/cosa+cosa/sina=3
=>
((sina)^2+(cosa)^2)/(sinacosa)=3
=>
sinacosa=1/3
=>
2sinacosa=2/3
=>
sin(2a)=2/3
4、
cosa*1/csca=1,
错,cosa*1/csca=cosa*sina
sina*tana=cosa,
错,cosa*tana=sina
1+sin²a=cos²a,
错,1-sin²a=cos²a
cosa/cota=sina
对,cosa/cota=cosa*tana=sina
5、
tan(pi/8)-tan(3pi/8)
=tan(pi/8-3pi/8)(1+tan(pi/8)tan(3pi/8))
=tan(-pi/4)(1+1)
=-2
6、
(1+tan75)/(1-tan75)
=(tan45+tan75)/(1-tan45tan75)
=tan(45+75)
=-根号3
7、
tan(A+B)=(tanA+tanB)/(1-tanAtanB)=tan(π/4)=1
=>
tana+tanb=1-tanatanb
=>
tana+tanb+tanatanb+1=2
=>
(1+tana)(1+tanb)=2
8、
原式
=1/(cosa)^2+1/(sina)^2
=1/(4/5)^2+1/(1-(4/5)^2)
=25/16+25/9
=625/144
9、
原式
=1/((cosa)^2*cos(2a)) * ((cota)^2+1-((cot(3a))^2+1))/(csc(3a))^2
=(sin(3a))^2*((csc(a))^2-(csc(3a))^2)/((cosa)^2*cos(2a))
=((sin(3a))^2*(csc(a))^2-1)/((cosa)^2*cos(2a))
=((sin(3a))^2-(sina)^2)/((sina)^2*(cosa)^2*cos(2a))
=(sin3a+sina)(sin3a-sina)/((sina)^2*(cosa)^2*cos(2a))
=2sin2acosa*2cos2asina/((sina)^2*(cosa)^2*cos(2a))
=4cos2a*sin2a*sina*cosa/((sina)^2*(cosa)^2*cos(2a))
=4sin2a/(sinacosa)
=8
10、
1+(tana)^4
=((tana)^2+1)^2-2(tana)^2
=(seca)^4-2(sina)^2/(cosa)^2
=(1/cosa)^4-2(1-(cosa)^2)/(cosa)^2
=(3/2)^4-2*(1-4/9)/(4/9)
=41/16